Increasing The Productivity Of Palm Sugar Through High Degree Of Crystalline Sugar Production - Deni Faisal Mirza; Devi Alvionita Alindra; Khomeiny Yunior (Publisher Cv. Inara, 2022)
One of the victims of Covid-19 is micro industry. The research team attempts to find the community of original palm sugar (sugar from sugar palm tree) industry which will be process to become gula semut (crystalline sugar). The location where the research and the public service are done is Deli Serdang Regency, North Sumatera. It seems that the farmers of palm sugar industry are decreasing in number in Deli Serdang so that the research team is interested in increasing the community of palm sugar farmers and industry in developing their micro business. Another objective of the research is to increase the welfare of the palm sugar farmers in Deli Serdang, North Sumatera, with good and qualified crystalline sugar so that its sales price increases and it can enter domestic and international markets. The research employs descriptive qualitative method. The data are gathered by conducting interviews and using Focus Group Discussion with stakeholders. Specifically, the sugar palm trees are used for hand-handle sap tapping which yields water that flows from the stem of sugar palm tree. The water is called palm water (juice of the sugar palm which when fermented turns into toddy and vinegar). It has numerous kinds of palm sugar and one of them is crystalline sugar processing. In this research, crystalline sugar is used as the innovation from palm sugar processing in the form of slabs because its sales value is very promising. The concept of marketing strategy applied in this research is the online and offline marketing.